Classification of stillbirths by relevant condition at death (ReCoDe): a cross sectional study at a rural tertiary care centre in Kerala, India - K. K., Ajini; K. R., Radha; R. P., Reena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Stillbirths account for a major proportion of perinatal deaths. The cause for a large number of stillbirths, remain unexplained. The ReCoDe system (classification of stillbirths by relevant condition at death) has helped to improve our understanding of the causes of stillbirths. We evaluated stillbirths and classified them by the ReCoDe system. The objective was to identify factors associated with stillbirths and to classify the causes of stillbirths using the ReCoDe system. Methods: We recruited all women admitted to a tertiary care centre with a diagnosis of intrauterine fetal death after 22 weeks of gestation. Maternal sociodemographic characteristics and relevant antenatal and intrapartum investigations were studied. We examined the stillborn babies, placenta and umbilical cord and classified them according to the ReCoDe system. Results: There were177 women with intrauterine fetal death admitted during the 2 year study period. The stillbirth rate was 38.56 per 1000 live births. We could explain the cause of stillbirth in 87.58% of cases by using the ReCoDe system. Intra uterine growth restriction (41.8%) was the commonest cause followed by hypertensive disorders (27.68%), congenital anomalies (15.81%) and diabetes (14.68%) in present study. Conclusions: We found the ReCoDe system useful in classifying the cause of stillbirths in resource limited settings.